Impact of land use (oil palm) on the fish fauna, macrobenthos and water quality of Kayan river and its tributaries, Lundu, Sarawak - Alvina, Grifin (Universiti Malaysia Sarawak, (UNIMAS), 2014)
This study was conducted to document the fish fauna composition and macrobenthos community structure as well as to detennine the impact of land use changes on water quality and to apply QUAL2K model to Kayan River. Six stations were selected for fish fauna and macrobenthos and ten stations for water quality at Kayan River and its tributaries. Sampling method used for fish was gill net of various mesh sizes and three layer gill net. Grab sampler and kick net were used for macrobenthos. Measurements of physico-chemical and biological parameters were carried out between June 2010 and September 2011. Six months data were used for calibration and five months data for validation. QUAL2K model simulation was used to predict pollution concentrations reduction in Kayan River A total of 456 fish individuals were caught comprising of 28 species, 19 genera and 10 families while 2,125 individuals of macrobenthos were sampled, comprising of 3 phyla, 4 classes and 12 families. The highest fish species diversity was at station I and highest species richness was at station 2 with a value of 1.096 and 8.274, respectively. All stations have similar community structure of macrobenthos which is dominated by Naididae family. Higher NHrN (1.62 mg/L), TKN (2.46 mg/L), TP (0.64 mg/L) and BODs (6.20 mg/L) at stations downstream of effluent input indicated the impact from emuent discharges. The average value of WQI in Kayan River was 80 which correspond to good water quality. However, average subindex for NH3-N (63) and TSS (66) were classified as polluted. Higher TSS and turbidity along the river were due to deforestation for oil palm plantation. Prediction results of TSS, NH3-N and BODs in Kayan River exceeded Class II NWQS limits ofTSS S50 mg/L, NH3-N SO.3 mg/L and BODs S3 mg/L if raw effluent and discharge limit of effluent is discharged into the effluent discharge tributary. QUAL2K model application shows that inflow concentrations for Class II compliance at the palm oil mill effluent receiving tributary for TSS, NH3-N and BODs were S I.O mg/L, SO.002 mg/L and SO.8 mg/L, respectively while from headwater concentrations are TSS (50.00 mg/L), NH3-N (0.20 mg/L) and BODs (3.00 mg/L). Fish fauna composition and macrobenthos community structures were affected by landuse and habitat characteristics while mill effluent and oil palm plantations are the main factors differentiating physical, chemical and biological variables of Kayan River.